A Modified Conjugate Gradient Method With Taylor Approximation: Applications In Electric Circuits And Image Restoration - Ahmad Alhawarat; Sultanah Masmali; Ibtisam Masmali; Mehiddin Al-Baali; Shahrina Ismail (New York Business Global, Maryland, USA, 2026)
Indexed by WOS / SCOPUS / ERA